Armenia : An Assessment of the Real Exchange Rate and Competitiveness - Weber, Anke (IMF Working Papers; Working Paper, 2011)
This paper uses a range of different methodologies to estimate the equilibrium real exchange rate in Armenia with both single-country and panel estimation techniques. We estimate a country specific autoregressive distributed lag model and then proceed with the estimation of a cointegrated panel consisting of transition economies in Europe and Central Asia. This addresses cross section dependence by using common correlated effects estimators. While our analysis focuses on Armenia, the methods are applicable to a large number of transition economies, and the paper thus provides an overview of methods that can be used to assess a country's equilibrium exchange rate.